Evaluasi Implementasi Kebijakan Penanganan Stunting oleh Dinas Kesehatan, Pengendalian Penduduk dan Keluarga Berencana Kota Tanjungpinang - Sri Ambar Rinah; Diah Siti Utari; Edward Mandala; Etika Khairina; Zamzami A. Karim; Neng Suryanti Nengsih (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Based on the latest data from 2024, the stunting problem in Tanjungpinang City includes a prevalence that is still high, with a figure of 15.2% in 2024. Stunting cases refer to several sub-districts, such as Pinang Kencana Subdistrict, Tanjung Unggat Sub-district, and Kampung Bugis Sub-district. The purpose of this study was to evaluate the implementation of stunting management policies by the Dinas Kesehatan, Pengendalian Penduduk dan Keluarga Berencana Kota Tanjungpinang. The study used a library research method as its primary approach. The data analyzed was secondary, namely information gathered from various sources such as scientific journals, books, and websites related to the research topic. Based on the evaluation of the implementation of stunting management policies in Tanjungpinang City, it can be concluded that the stunting management program implemented by the Dinas Kesehatan, Pengendalian Penduduk dan Keluarga Berencana Kota Tanjungpinang. has shown positive progress. This is demonstrated by a decrease in the stunting prevalence rate from 15.7% in 2022 to 15.2% in 2023.